2006 IEEE Conference on Electrical Insulation and Dielectric Phenomena 2006
DOI: 10.1109/ceidp.2006.311992
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Acid-Water Aging of RTV Silicone Rubber Coatings

Abstract: The paper reports on tests done on four commercial room-temperature vulcanized (RTV) silicone rubber high voltage insulator coatings aimed at achieving information on the relative performance of the coatings and the effect of acid-water on the surface degradation. The initial characterization of the coatings includes the identification of the primary filler type, concentration of filler, the amount of free fluid, and the molecular make-up of the free fluid. Soxhlet extraction and gas chromatography tests show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kemaloglu et al researched the effect of different llers on the thermal property of SIR [8]. Jahromi et al reported the effect of surface degradation of silicone rubber for the high voltage insulator coating [9]. KAMIYA et al declared the effect of secondary crosslinking reaction on the initial voltage of the electrical branch in SIR dielectric and found that the tree voltage of SIR increases after the degassing process and it decreases after the process of reaeration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kemaloglu et al researched the effect of different llers on the thermal property of SIR [8]. Jahromi et al reported the effect of surface degradation of silicone rubber for the high voltage insulator coating [9]. KAMIYA et al declared the effect of secondary crosslinking reaction on the initial voltage of the electrical branch in SIR dielectric and found that the tree voltage of SIR increases after the degassing process and it decreases after the process of reaeration [10].…”
Section: Introductionmentioning
confidence: 99%